2010
DOI: 10.1007/s11136-010-9653-1
|View full text |Cite
|
Sign up to set email alerts
|

Self-efficacy, adjustment style and well-being in breast cancer patients: a longitudinal study

Abstract: Self-efficacy was a significant predictor of an active adjustment style and emotional well-being in breast cancer patients. Hence, it could be a valuable target of rehabilitation programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
109
4
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(121 citation statements)
references
References 45 publications
5
109
4
3
Order By: Relevance
“…[109][110][111][112][113][114] However, little is known about changes over time, and the direction of relationships or potential causal mechanisms have not been studied. In one longitudinal study, SE predicted quality of life post-injury, suggesting that strengthening SE might enhance life quality.…”
Section: Discussionmentioning
confidence: 99%
“…[109][110][111][112][113][114] However, little is known about changes over time, and the direction of relationships or potential causal mechanisms have not been studied. In one longitudinal study, SE predicted quality of life post-injury, suggesting that strengthening SE might enhance life quality.…”
Section: Discussionmentioning
confidence: 99%
“…There is no significant correlation between fighting spirit and the QoL in other studies. Because of the relation between fatalism and QOL, some studies showed that it was a negative relation (20,21), while others showed a positive relation (22,23) or no significant correlation (24).…”
Section: Introductionmentioning
confidence: 99%
“…자기효능감은 바람직한 효과를 산출하는 행동을 성공적 으로 수행할 수 있다는 개인의 믿음으로 [5], 유방암 환자의 적 극적인 적응 과정에 가장 강력한 영향요인이며 [6], 자가간호행 위에 매우 중요한 요인으로 보고되고 있다 [7]. 유방암 생존자 에서 자기효능감은 투병의지, 희망, 신체적 ․ 정서적 ․ 사회적 기 능과 유의한 상관관계를 나타내고 있으며 [6], 일부 선행연구에 서는 자기효능감과 피로, 디스트레스와의 유의한 관련성이 있 는 것으로 보고되고 있다 [8][9][10]. …”
unclassified